2015
DOI: 10.1088/1468-6996/16/5/055005
|View full text |Cite
|
Sign up to set email alerts
|

Engineered silica nanoparticles as additives in lubricant oils

Abstract: Silica nanoparticles (SiO2 NPs) synthesized by the sol–gel approach were engineered for size and surface properties by grafting hydrophobic chains to prevent their aggregation and facilitate their contact with the phase boundary, thus improving their dispersibility in lubricant base oils. The surface modification was performed by covalent binding of long chain alkyl functionalities using lauric acid and decanoyl chloride to the SiO2 NP surface. The hybrid SiO2 NPs were characterized by scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…As nanolubricants require a long time to become stable, methods have been reported to examine dispersion in time. The widely used method is visual inspection [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The lubricant dispersed with nanoparticles is visually different compared to a lubricant.…”
Section: Dispersion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As nanolubricants require a long time to become stable, methods have been reported to examine dispersion in time. The widely used method is visual inspection [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The lubricant dispersed with nanoparticles is visually different compared to a lubricant.…”
Section: Dispersion Methodsmentioning
confidence: 99%
“…APTEOS [17,124] or DETAS [16,40] was used in this process. The second step was to bond a carboxylic acid surfactant, such as lauric acid [17] or stearic acid [16,40,124], to the amino group. This method grafted long alkyl chains on the silica surface without the use of expensive ODTS (octadecyltrichlorosilane).…”
Section: Other Methodsmentioning
confidence: 99%
“…Silica is widely used as additives in lubricant oils in machineries and motorised vehicles. Nano-lubricants are extensively used to reduce the friction, heat and wear between mechanical components (López et. al, 2015).…”
Section: Silica Dioxide Nanoparticles In Lubricants Oilmentioning
confidence: 99%
“…Nanoparticles and materials in nanoscale have a gained great deal of attention in the last two decades due to their unique and special properties which are not shown by bulk materials, they have several applications in many fields such as catalysts [1], solar [2], optoelectronic and imaging [3], and thin film coating [4,5]. Recently, nanomaterials have been used in lubricant as additives to improve its physical and tribological properties rather than pure lubricant [6][7][8][9][10]. Bhaumik et al investi gated the wear reduction of CuO nanoparticles additives in mineral oil using pin on disk apparatus and they observed that (0.2 wt %) of CuO nanoparticles decreased the fraction coefficient by (28.5%) and reduced the wear rate by (70%) as compared with pure mineral oil [6].…”
Section: Introductionmentioning
confidence: 99%
“…Twist et al reported that pyrazolepyridine silver complex is evaluated as friction reducing agent and antiwear additives in engine oil at temperature which thermally degrades the base oil [8]. Grafting hydrophobic SiO2 nanoparticles used by López et al as a lubricant additive and they found these nanoparticles reduce drastically the waste of energy in fraction process and more environmentally friendly than other additives [9]. Ratoi et al in another study proposed the mechanism of using WS2 as a lubricant additive in high pressure contacts and they observed a uniform tribofilm was generated lead to reduce both fraction and wear in high pressure sliding contacts [10].…”
Section: Introductionmentioning
confidence: 99%